Enhanced depth imaging is less suited than indocyanine green angiography for close monitoring of primary stromal choroiditis: A pilot report - Balcı, Özlem; Gasc, Amel; Jeannin, Bruno; Herbort, Carl P., Jr. (Springer, 2017)
The purpose of this study is to investigate the performance, utility, and precision of enhanced depth imaging optical coherence tomography (EDI-OCT) versus indocyanine green angiography (ICGA) in tracking any fluctuation in the activity of stromal choroiditis in response to therapeutic interventions during long-term follow-up. Patients with a diagnosis of Vogt-Koyanagi-Harada (VKH) disease or birdshot retinochoroiditis (BRC), with untreated initial disease, and having had long-term follow-up, including both ICGA and EDI-OCT, were recruited at the Centre for Ophthalmic Specialised care, Lausanne, Switzerland. Angiography signs were quantified according to established dual fluorescein angiography (FA) and ICGA scoring systems for uveitis. Changes in ICGA score and EDI choroidal thickness, in response to therapeutic intervention, were assessed. In the four eyes analysed (2 BRC and 2 VKH), mean EDI-OCT choroidal thickness decreased from 672 +/- 101 A mu m at presentation to 358.5 +/- 44.5 A mu m in a mean of 26.5 months, i.e. the time taken to stabilize the disease. Mean ICGA scores decreased from 28 +/- 4.2 at presentation to 5 +/- 7 at stabilization. Only ICGA was sufficiently sensitive and reactive having the ability to detect disease recurrences and efficacy or the absence of effect of successive treatment changes, detected in seven instances during follow-up, not recorded by EDI-OCT. This pilot study showed that ICGA was a more sensitive methodology, which promptly identifies evolving subclinical and occult choroidal disease, and flag occult recurrence and/or therapeutic responses that were otherwise missed by EDI-OCT. Although choroidal thickness was proportional to treatment course, demonstrating a linear decrease, these changes were too sluggish to be relied upon for close follow-up and timely adjustment of therapy.
WOS: 000401918500038
PubMed ID: 27486023
Keywords: Stromal Choroiditis; Vogt-Koyanagi-Harada Disease; Birdshot Retinochoroiditis; Indocyanine Green Angiography; EDI-OCT; Uveitis Monitoring